TINEA OF THE PENIS – A RARE LOCALIZATION OF A DERMATOPHYTE INFECTION - Bjekic, Milan; Stojkovic, Marina; Pecarski, Danijela (HEALTH CARE, 2023)
Background/Aim: Dermatophyte infection of male genitalia is not common and the aim of this paper is to show the rare localization of this disease on the shaft of the penis in a healthy man. Case report: We present a 34-year-old man with pruritic annular erythematous scaly patch on the shaft of the penis. There are no other skin lesions. Sample preparation of changes from the body of the penis made with the addition of potassium hydroxide is positive, and culture revealed Trichophyton mentagrophytes. The patient was treated with a topical antifungal therapy for two weeks and skin lesions resolved. Conclusion: Although genital localization of dermatophyte infection is rare, this disease should be considered, diagnosed and treated early otherwise it may become a focus for recurrent fungal infections